A phase 1, randomized, placebo-controlled study to evaluate the safety and immunogenicity of an mRNA-based RSV prefusion F protein vaccine in healthy younger and older adults - Aliprantis, Antonios O.; Shaw, Christine A.; Griffin, Paul; Farinola, Nicholas; Railkar, Radha A.; Cao, Xin; Liu, Wen; Sachs, Jeffrey R.; Swenson, Christine J.; Lee, Heather; Cox, Kara S.; Spellman, Daniel S.; et al. (Human vaccines & immunotherapeutics, 2021)
Respiratory Syncytial Virus (RSV) causes lower respiratory tract infections that can be severe and sometimes fatal. The risk for severe RSV infection is highest in infants and older adults. A safe and effective RSV vaccine for older adults represents a serious unmet medical need due to higher morbidity and mortality in this age group. In this randomized, partially double-blind, placebo-controlled, phase 1 dose-escalation study, we evaluated the safety, tolerability and immunogenicity of an investigational messenger ribonucleic acid (mRNA) vaccine encoding the RSV fusion protein (F) stabilized in the prefusion conformation. The study was conducted in healthy younger adults (ages ≥18 and ≤49 years) and healthy older adults (ages ≥60 and ≤79 years). Participants received mRNA-1777 (V171) or placebo as a single intramuscular dose. For each dose level, three sentinel participants were administered open-label mRNA-1777 (V171). Seventy-two younger adults were randomized and administered 25, 100, or 200 µg mRNA-1777 (V171) or placebo, and 107 older adults were randomized and administered 25, 100, 200 or 300 µg mRNA-1777 (V171) or placebo. Primary objectives were safety and tolerability and secondary objectives included humoral and cell-mediated immunogenicity. All dose levels of mRNA-1777 (V171) were generally well tolerated and no serious adverse events related to the vaccine were reported. Immunization with mRNA-1777 (V171) elicited a humoral immune response as measured by increases in RSV neutralizing antibody titers, serum antibody titers to RSV prefusion F protein, D25 competing antibody titers to RSV prefusion F protein, and cell-mediated immune responses to RSV-F peptides.